Oyster seedling growing method - SUN XIAOFENG (2016)
The invention discloses an oyster seedling growing method comprising the following steps: 1, field selection; 2, field sorting; 3, seeding season; 4, seeding. The oyster produced by the novel method is strong in body, large in size, even in spatfall, and fast in growth. 本发明公开种牡蛎养殖方法，包括下列步骤：(1)场地选择；(2)场地整理；(3)播苗季节；(4)播苗，本发明提供种牡蛎养殖方法，具有体质健壮、个体大、附苗均匀、生长快等特点。